Dabrafenib–trametinib combination in 'field-practice': an Italian experience. (7th August 2018) - Depenni, Roberta; De Rosa, Francesco; Greco, Stefano; Ridolfi, Laura; Pellacani, Giovanni; Ponti, Giovanni; Cascinu, Stefano; Guidoboni, Massimo
Aim: This observational study investigates the effectiveness and safety of dabrafenib/trametinib combination in patients with metastatic melanoma.Patients & methods: Seventy-six patients treated with dabrafenib/trametinib (150 mg twice daily/2 mg once daily) were included.Results: Median progression-free survival was 9 months (95% CI: 7–11) and median overall survival was 14 months (11–16); disease control rate was 72%. Nine patients (12%) experienced a complete response. Of these, seven presented one metastatic site, none had lung or CNS metastasis, and none had elevated baseline lactate dehydrogenase (LDH) levels. Overall, subgroup analysis for patients with adverse prognostic features led to similar results. No new safety signals were reported.Conclusion: Dabrafenib/trametinib combination can be effective and well-tolerated also in a heterogeneous 'real life' population comprising patients with adverse prognostic features.